Frontispiece: Electrochemically Triggered Chain Reactions for the Conversion of Furan Derivatives. Issue 14 (22nd March 2021) - Chen, Rong; Yang, Cangjie; Zhou, Zefeng; Haeffner, Fredrik; Dersjant, Alinda; Dulock, Nicholas; Dong, Qi; He, Da; Jin, Jing; Zhao, Yanyan; Niu, Jia; Wang, Dunwei
Abstract : Biomass Conversion An electrochemical method for the coupling of biomass‐derived C5 /C6 compounds to value‐added fuel precursors is described by Jia Niu, Dunwei Wang et al. in their Communication on page 7534 .